If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 3 + -7(x + 3) Reorder the terms: 3 = 3 + -7(3 + x) 3 = 3 + (3 * -7 + x * -7) 3 = 3 + (-21 + -7x) Combine like terms: 3 + -21 = -18 3 = -18 + -7x Solving 3 = -18 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 3 + 7x = -18 + -7x + 7x Combine like terms: -7x + 7x = 0 3 + 7x = -18 + 0 3 + 7x = -18 Add '-3' to each side of the equation. 3 + -3 + 7x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + 7x = -18 + -3 7x = -18 + -3 Combine like terms: -18 + -3 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| y=2+7(0.2121212121) | | a=-9+x+1y | | 2g+h=4 | | x+12=3x-7 | | 2d+4=10-5d | | 3(x+7)=25-(2-x) | | 11+10x=81 | | 17=r-9 | | 6-(v-4)=2(6v-3) | | 11+10x=81 | | 6-(v-4)=2(6v-3) | | 17=r-9 | | 7x+14y=13 | | 30=3x^2+1x | | 79=m+34 | | 4x-4=64 | | 3.4*6.2= | | (4.5x-5)-(8.3x-9)= | | 12k=84 | | x^2-8-11=0 | | 18w-10-bw=50 | | 2x+3=5(2+7x) | | 0=12x^2+5x+7 | | 5=m+6 | | 2+(-4)+6(2)=3(2)-1+5 | | 0=121x^2+5x+7 | | 0=121x^2+5x+7 | | 15x^2+7x+6=0 | | 9ln(7x)=45 | | 15-5g=-33.5 | | 57=d-12 | | 3(m+4)-12=15 |